ПОСТПІРОГЕННА ДИНАМІКА РАДІАЛЬНОГО ПРИРОСТУ В СЕРЕДНЬОВІКОВОМУ СОСНЯКУ РІВНЕНСЬКОГО ПОЛІССЯ - Voron, V. P.; Koval, I. M.; Tkach, O. M.; Sidorenko, S. G. (Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky (URIFFM), 2018)
Introduction The problem of fires in Polissya forests is associated with the abnormal number of hot and dry days during some periods. To our knowledge, features of pine radial growth in stands after fires as an integral indicator of forests health and productivity are almost unexplored at this time. The aim of the study is to examine the dynamics of Scots pine (Pinus sylvestris L.) radial growth in the fire-damaged stand in Rivne Polissya zone. Materials and Methods Comparison of effects of the fire occurred at the beginning of May 2013 was carried out using two permanent plots laid out in undamaged and damaged parts of the 70-year-old pine stand using techniques, generally accepted in forestry and forest inventory. Radial growth of pine forests damaged by fire was studied using traditional dendrochronology methods. Based on the root-mean-square deviation from the average multi-year temperature and precipitation (from 1945 to 2015), the criteria for anomalous weather conditions were calculated. Results and Conclusions At the damaged part of the pine stand, bark char on a trunk ranged from 0.85–4.00 m, and two months later after the fire, the health condition of the stand was assessed as «dying forest». Radial growth of fire-damaged stands ranged from 0.87 to 1.23 or averaged 0.93 mm per year. For control, it was slightly higher, 0.90–1.05 and 0.96 mm in average per year. During this period, the average values of spring wood in both pine stands were the same but the average values of summer wood were slightly higher in the control plot. Minimum value in both cases occurred in 2009 and 2011. These years were assessed as “dry years” due to the poor precipitation during the growing season. In general, in the damaged stand, the radial growth after the fire reduced by 32 % compared with the period before the fire. At the same time, in the control plot, the average radial growth increased by 5% during this period. Taking into account the precipitation amount and hydrothermal index, the vegetation period in 2013 can be considered as «normal» but April, July, and August were «dry». As a result of the fire, which occurred in the first decade of May 2013, spring wood growth decreased from 0.51 mm per year in 2012 to 0.47 mm per year in 2013 or by 8 %. At the same time, there was a significant decrease in summer wood growth up to 0.17 mm per year that is 2.1 times less than in 2012. When comparing the thickness of the spring and summer wood layers in the control after the fire (2013–2016) and before the fire damage (2009–2012), a small (from 2 to 9 %) increase was observed. At the same time, for the fire-damaged pines, the growth of spring wood layers decreased to 21 % and of summer wood layers, to 49 %. In 2014, weather conditions for the vegetation period were more favorable as compared to 2013. As a result, wood growth increased by 20 % at control plot. Positive changes were less pronounced in the fire-damaged part of the stand (4 % only). Due to anomalous weather conditions during vegetation period in 2015 and 2016, the radial growth decreased in the control plot but the especially noticeable decrease in the growth was observed in 2015 and 2016 in pine stands damaged by the fire: 17 and 25 % respectively compared to 2014. The thickness of the summer wood layer for damaged trees was 2.0–2.8 times less than in the control plot. Before the fire, summer wood percentage ranged from 32.7 to 45.7 % of the total thickness of the annual growth ring in the studied pine stand, and these values were close to the control (from 35.6 to 48.4 %). After the fire, the value decreased to 27.0–33.7 % (in the control part of the stand it was 36.1–48.1 %). In other words, summer wood was more sensitive to fire damage as evidenced by the differences in the average values before and after the fire in the damaged plot. The analysis showed a sharp decrease in radial growth: 32 % for severely weakened trees and 18 % for dying trees. Next year (2014) a slight increase in the radial growth was noticed for weakened trees in contrast to the dying ones, for which the radial growth decreased. Strong correlation between the indexes of radial growth and the minimal scorch height at 0.05 significance level (r = 0.79, tf = -2.72, tt = 2.46) were founded. In a year when forest fire occurred, radial growth for dominant trees decreased by 35 % and for co-dominant and sub-dominant ones, by 25 and 36 % respectively. In the next year (2014), radial growth increased for dominant (16 %) and sub-dominant (3 %) trees contrary to co-dominant trees, for which low radial growth was detected in 2015. In other words, in the last two years (2015–2016) the radial growth of all trees had not been resumed. A regression model was developed for the dependence of the pine radial growth indices on the height of the minimum scorch on the trunks. 7 Figs., 6 Tables, 19 Refs.